Optimization Of MSME Sector For Accelerating Regional Development: An Empirical Case Study Of Jabodetabek Agglomeration Area - Satrianto, Heri; Wicaksono, Baghas Budi; Kusnawan, Agus (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This study elaborating the optimization of MSMEs as a key driver of regional development in the Jabodetabek Agglomeration Area, emphasizing their vital role in shaping local economy performance. Using a quantitative approach that integrates collecting secondary data and processing with STATA Software, this research highlights its finding to find which variables that most determine MSME performance in Jakarta agglomeration area. MSMEs generate employment, promote market stability, and foster innovation, offering affordable and competitive alternatives that enhance access to goods and services for diverse income groups. By controlling inflation through price-competitive products. Policymakers can leverage the potential of MSMEs to achieve sustainable regional development by reducing reliance on external markets and enhancing local economic resilience. This research results provide findings that MSMEs not only address immediate economic needs but also establish a foundation for long-term regional sustainability. Their contributions to economic inclusivity, innovation, and resilience make them a cornerstone of balanced, sustainable, and inclusive economic growth in the Jabodetabek region.